From Soviet to Europe: Returns to education puzzle in Bulgaria - Anita Staneva; Hany Andel-Latif (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2015)
This paper makes a systematic presentation of returns to education in Bulgaria, a country that has witnessed a number of dramatic structural changes over the last two decades. It examines the headway of returns to education for Bulgaria in two obverse economic regimes - from communism to EU membership. The findings show a steady increase in returns to education for both males and females until 2003. The average returns to one additional year of education rose from 1.1% in 1986 to 5.1% in 2003 for males and from 2.1% to 5.9% for females. Quantile regression estimations, between 1986 and 2003, evince that the most prominent increase in the wage premium occurred at the top end of the distribution, where the rate of returns to education, in particular for females increased from a negative and insignificant sign in 1986 to 7% in 2003. However, this increasing trend in returns to education seems to take an inverted-U-shape in 2007, the year when the country joined the EU, which poses a new puzzle to be resolved. To this end, the current paper introduces possible explanations for such a puzzle and sheds lights on a number of insightful policy implications.
Keywords: I21; J31; 330; returns to education; transition countries; quantile regression